Designer notoriety: What the Lubitz case tells us about the accumulation of attention capital in celebrity culture. (February 2020) - Rojek, Chris
This article introduces the concept of designer notoriety to refer to calculated attempts to derail aspects of normative order so as to garner media attention. The objective is for otherwise unexceptional people to gain celebrity. The case of the alleged sabotage of Germanwings Airbus A320 Flight, by the co-pilot, Andreas Lubitz, in 2015, is used as a case study. Drawing on the methods of content analysis from various media sources and historical sociology, the article examines the media claim that Lubitz sought celebrity and planned the crash as a means to acquire media interest. Public receptivity to the notion of designer notoriety is investigated. It is related to three key concepts: 'the demotic turn', 'mediatization' and the 'world historic event'. The application of each concept to designer notoriety is set out and justified. The article ends by expanding the Lubitz case to refer to other examples of designer notoriety.